2022
DOI: 10.1021/acsnano.2c04774
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Specific Binding of 4 nm Lipid Nanoparticles Mediated by an Entropy-Driven Interaction Mechanism

Abstract: Lipid nanoparticles (LNPs) are a leading biomimetic drug delivery platform due to their distinctive advantages and highly tunable formulations. A mechanistic understanding of the interaction between LNPs and cell membranes is essential for developing the cell-targeted carriers for precision medicine. Here the interactions between sub 10 nm cationic LNPs (cLNPs; e.g., 4 nm in size) and varying model cell membranes are systematically investigated using molecular dynamics simulations. We find that the membrane-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…621 Recently, the preferential binding of NPs on membranes of various compositions was found to be an entropydriven process. 622 The gel-phase membrane patch is stiffer and more resistant to bending, as analyzed by previous simulations. 623 Thus, NPs are more challenging to be wrapped by the gel-phase membrane, due to the higher energy cost of membrane bending.…”
Section: Pathways Of Nm−cell Membrane Interactions From MD Nm−cell Me...mentioning
confidence: 69%
“…621 Recently, the preferential binding of NPs on membranes of various compositions was found to be an entropydriven process. 622 The gel-phase membrane patch is stiffer and more resistant to bending, as analyzed by previous simulations. 623 Thus, NPs are more challenging to be wrapped by the gel-phase membrane, due to the higher energy cost of membrane bending.…”
Section: Pathways Of Nm−cell Membrane Interactions From MD Nm−cell Me...mentioning
confidence: 69%
“…[ 79 ] Moreover, these unsaturated alkyl chains can also act as immunomodulators by contributing to membrane destabilization and fusogenicity. [ 80–82 ] Ou et al. reported that a higher extent of unsaturated cationic lipids in LNP facilitates membrane contact and increases the membrane‐binding probability than analogous LNP with saturated cationic lipids.…”
Section: Lnp As a Versatile Platform For Rna Encapsulation And Deliverymentioning
confidence: 99%
“…The authors also demonstrated that increasing the degree of unsaturation in lipid tails yields LNP with a loosely packed structure and promotes lipid exchange at the membrane, which was verified by calculation of the lipid exchange rate and increase of entropy. [ 82 ] In fact, a low degree of saturation in lipids leads to a low transition temperature and thus facile formation of inverted micelles, and even inverted hexagonal lipid phase (H II ). For instance, synthetic spermine‐derived lipopolyamines with a lower degree of saturation have shown increased gene silencing efficiency.…”
Section: Lnp As a Versatile Platform For Rna Encapsulation And Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 With specific coating lipids, these NPs demonstrate excellent targeting abilities for membranes and even tissues, showing great potential in precision medicine. [23][24][25][26][27][28] However, given the intricate nature of biological processes and the growing need to expand the potential biomedical applications of NPs, further efforts are required to develop novel regulatory strategies for NP cellular uptake, such as exploring new NP species or properties and investigating alternative modes of membrane-NP interactions. [29][30][31][32][33][34][35] Photothermal therapy (PTT) has garnered significant attention in recent years as a promising noninvasive technique for tumor treatment.…”
Section: Introductionmentioning
confidence: 99%